Digital Content Creative sebagai Media Informasi melalui Instagram dalam Penerimaan Mahasiswa Baru di STAHN Mpu Kuturan Singaraja - Niluh Wiwik Eka Putri; I Gede Titah Pratyaksa (Universitas Merdeka Malang, 2024)
STAHN Mpu Kuturan Singaraja promotes PMB via social media Instagram through digital content creative. The aim of the research is to determine the role of digital content creative in the model used is the Luther model which consists of concept, design, material collecting, assembly, testing and distribution. The method used in this research is pure qualitative descriptive with a phenomenological approach. The theories used include Excellence theory. The research results include the first post using the Two-Way Symmetric model which prioritizes feedback from the community. Meanwhile, the second post also uses the Two-Way Symmetric model. Furthermore, the third post uses the Public Information model, which aims to build public trust through one-way communication. Meanwhile, the fourth post also uses the Public Information model. Next, the fifth post uses the Press Agentry / Publicity model.